Effects of different drying methods on the antioxidant activities of leaves and berries of cayratia trifolia - Rabeta, M.S.; Lin, S.P. (Universiti Kebangsaan Malaysia, 2015)
This study aimed to assess the effects of fresh, thermal drying method (vacuum oven drying), and nonthermal drying method (freeze drying) on the antioxidant activities of leaves and berries of Cayratia trifolia using ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-1-picrylhydrazyl radical scavenging capacity (DPPH) assays. The total phenolic content (TPC) and flavonoid content (TFC) of the leaves and berries of C. trifolia were also measured. Based on the results obtained, the TPC, TFC, and antioxidant activities of the leaves and berries were arranged in the following order: freeze-dried sample with methanol extraction > vacuum-dried sample with methanol extraction > freeze-dried sample with water extraction > vacuum-dried sample with water extraction > fresh sample with methanol extraction > fresh sample with water extraction. The results showed a significant difference (p<0.05) between the fresh and dried samples. In conclusion, freeze drying was found to be a good method for maintaining TPC, TFC, and antioxidant activities by FRAP and DPPH methods in the leaves and berries of C. trifolia.